An Evaluation of the Relationship between the Pleth Variability Index with Bleeding and Volume Responsiveness in Patients Undergoing Lumbar Spine Surgery Under General Anesthesia - Maziar Motemanni Sharabiani; Khalil Pestei; Laya Amoozadeh; Leila Sahebi; Farhad Etezadi; Mojgan Rahimi (Archives of Anesthesia and Critical Care)
Background: Pulse oximetry is essential for monitoring patients during surgery, which display SPO2, as well as the plethysmographic variability index. Volume responsiveness is also indicated by this index. Considering the non-invasiveness of the PVI index and its predictive value, its use could be highly beneficial. Thus, we decided to evaluate the correlation between Pleth Variability Index in prone position and bleeding and volume responsiveness in patients undergoing lumbar spine surgery under general anesthesia. Methods: 119 patients who were candidates for lumbar spine fixation surgery were studied in the prone position during surgery. Aside from demographic information, vital signs and PVI levels were recorded after induction of anesthesia, 5 minutes after induction of anesthesia, immediately after changing position from supine to prone, 5 minutes after changing position from supine to prone, at the end of the operation, immediately after shifting position from prone to supine, and after switching position from prone to supine for 5 minutes. Accordingly, the amount of bleeding and the type and amount of fluid received during the operation were recorded. Results: Results revealed that demographic factors (gender, age, weight, height), hemodynamic factors (heart rate, blood pressure, SPO2), cardiac EF, and initial Hb levels, and changes in position from supine to prone did not affect the PVI process. In contrast, PVI has decreased due to an increase in intraoperative fluid intake. Notably, the amount of fluid received by different people (taking into consideration weight, bleeding, etc.) had no effect on PVI decreasing. Conclusion: The PVI provides a cheap and readily accessible way to determine volume responsiveness, which is unaffected by various individual variables and can be performed in a prone position.